Atsaru Istikhkdam Uslub al-Pedagogiyah al-Fariqiyah Fi Tahqiq Ahdaf Ta'lim al-Lugahh al-Arabiyyah bi al-Marhalah al-Asasiyyah Fi Nigeria: Impact Of Differentiated Pedagogy Approach Towards Achieving Objectives Of Teaching Arabic Language At The Elementary School In Nigeria - Garba, Ahmad (Jurnal Pendidikan Bahasa Arab dan Budaya Islam, 2024)
The term differentiated pedagogy is an educational technique that uses a variety of teaching-learning methods in order to help children of different ages, abilities, and behaviors, and who belong to one class, to reach the desired educational goals in different ways. This means that this approach believes in the existence of individual differences between learners. adapting the teaching and learning process according to their specifications, in order to make every individual within the classroom achieve the goals set for him. On this basis, this paper aims to reveal the extent of the impact of differentiated pedagogy in achieving a specific teaching- learning goals regarding teaching Arabic language in the lower level of primary schools in Nigeria, to achieve that objective, the researcher used descriptive research design, the final result indicates that there is a positive impact in using the differential pedagogy in achieving a specific objectives in teaching Arabic language in primary schools. Especially teaching Arabic language in the lower level of primary school in Nigeria.